STRATEGI KOMUNIKASI SATUAN TUGAS PENANGANAN COVID-19 DALAM PENCEGAHAN PENYEBARAN COVID-19 DI KOTA PEKANBARU - Ferdy Syaflansein; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACK Pekanbaru city is one of region that has impact of Covid-19 pandemic. By the commnication with the citizen of Pekanbaru city, the handling task force of covid 19 has the effective communication strategy in implementing this handling process of covid 19 pandemic. Therefor, the goal of this research is used to know how the communication strategy of the covid 19 handling task force in preventing the covid 19 pandemic in Pekanbaru city. The purpose of this research is to recognize the communication strategy of handling task force of Covid 19 for preventing of Covid 19 pandemic in Pekanbaru city in the phase of the communicator determination, the public knowing, the message arranging, the communication media choice and the respons. In this research, the subject is the Pekanbaru’s society according to the criteria namely the society that has implemented the rules and broken the rules of Covid 19 prevention meanwhile the object is the communication strategy of handling task force of Covid 19 for preventing Covid 19 pandemic in Pekanbaru. The researcher uses the theory of communication strategy according to harold D. Lasswell for describing the communication activity that answers the questions from Who (who is the communicator), Says what (what message that is conveyed), In which channel (which media that is used), To whom (who is the communicant), and With what effect (which impact that is hoped). The research methode that is used in this thesys writing namely using the research methode of descriptive qualitative and the field research, namely the method of observation, interview, and documentation. Thus, the researcher analyzes the data by the methode or reduction, data presentation, and verification to obtain the hoped data. The result of this research shows that the communication strategy that is implemented by the task force chairman decides to choose the chairman as communicator. The communicant is the people of Pekanbaru namely religion figure, all the head of neighborhood association and citizens association, task force member, and local security. The education, socialization, and social media are the message delivery strategy by the task force of Covid 19 in Pekanbaru. The andemic condition makes the internet media as more constructive, effective and efficient media by delivering the message of Covid. And the respond against handling Covid 19 is positive and negative. Keywords: Communication Strategy, Handling Task Force, Covid-19